EFFECT OF HUMIC ACID AND EM1 FERTILIZERS ON GROWTH AND YIELD OF TWO CUCUMBER CULTIVARS (CUCUMIS SATIVUS L.) UNDER PLASTIC HOUSE CONDITIONS. - RASHEED, SANAA M.S.; AHMED, JAMIAA MOHAMMED; DIN, OMEED MOHAMMAD; FAREEQ, SUHAILA RAFEEQ (Journal of Duhok University, 2020)
This experiment was conducted in the plastic house at the vegetable research farm of Directorate of Agricultural Extension and Scientific Research of Dohuk, Kurdistan region/ Iraq, during the growing Seasons of 2018-2019, to investigate the effects of Humic acid, (0.8 g.l-1and 1.6 g.l-1) and EM1 (3 ml.l-1and 6ml.l-1) in addition to the Control on growth and yield of two Cucumber cultivars (Falcon star and Sayfi F1). The results shows that Falcon star was superior over to Sayfi F1 in plant length and chlorophyll in leaves in fall season (2.91cm and 51.76SPAD), while Sayfi Fi overcome to Falcon star on chlorophyll in leaves, fruit diameter in spring season (47.40SPAD and 2.90cm). No significant effect of fertilizers had been seen in vegetative characters. But the yield characters had significant effects, the 3ml.l-1 of EM had higher value of Fruit weight 111.71g in spring season, while 6ml.l-1of EM had higher (Plant yield 5.36Kg and Total yield 139.51 ton.ha-1) in fall season. Control treatment had higher fruit length and diameter (17.01cm and 2.91cm) in spring season.